Utilization of Instagram Social Media in Marketing Assisted MSME Products in Ciater Village, South Tangerang - Ratna Komala; Annisa Ratu; Bagus Anggoro Prasetyo (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In running their business, the Micro, Small and Medium Enterprises (MSME) group under the supervision of the Ciater sub-district, in South Tangerang still uses traditional methods, and does not yet know and utilize social media, such as Instagram. Even though Instagram can promote businesses with the potential to reach a wider and more interesting audience because users can share photos, videos and integrate them with social networks such as Twitter and Facebook. Through socialization and outreach activities on the importance of using Instagram to MSME business actors in Ciater Village, South Tangerang City, which is carried out in Community Service activities, Pamulang University, it is hoped that there will be a transfer of knowledge and strategies for using social media to market MSME products. The activity method in the form of training is carried out interactively, starting with a presentation of material related to the benefits of Instagram in marketing MSME products, followed by questions and answers and ending with direct practice by participants, such as techniques for operating Instagram via participants' cellphones. The results of this counseling can directly motivate them to immediately create an Instagram account and they can start by making a product marketing plan via Instagram.